Study of Spinal anesthesia in patients with Scoliosis at a tertiary hospital - Goel, Akshi; Jeelani, Tahleel Mohd; Saleem, Basharat (Asian Journal of Medical Sciences, 2021)
Background: Scoliosis is a complex deformity of the vertebral spines resulting in lateral curvature, rotation of the vertebrae and deformity of the rib cage. 75 -90% of cases of scoliosis are of the idiopathic type, out of which the adolescent type is most common. Patients with scoliosis present challenges in administration of anesthesia during surgical procedures. The common problems are airway management and respiratory conditions. Aims and Objectives: The present study was aimed to study spinal anaesthesia in patients with scoliosis at a tertiary hospital. Materials and Methods: The present study was a prospective, observational study conducted in department of anesthesiology, in patients between age group 18 and 60 years with scoliosis (Cobb’s angle of >15°), American Society of Anesthesiology physical grade I/II, posted for elective, lower limb orthopedic soft tissue release procedures under spinal anesthesia. All details were noted in case proforma and entered in Microsoft excel sheet. Statistical analysis was done using descriptive statistics. Results: A total of thirty-two patients were included in present study. The mean age was 25.27 ± 4.81 years. Male (63%) were more than female (37%). Male to female ratio 1.7:1. As per American society of anaesthesiologist physical grading grade I patients were 78% while grade II was 22%. The onset of sensory block was in 7.9 ± 2.3 mins and onset of motor block was in 4.9 ± 2 mins. Maximum extent of sensory blockade till T5-T4 was noted in 66% patients. Time taken for complete recovery of motor block to its preoperative level was 94.3 ± 26.2 min. Conclusion: With proper preoperative assessment, spinal anesthesia can be safely used in patients with scoliosis. Patients with scoliosis needs good preoperative assessment, well equipped setup and team efforts for good outcome.